Analyzing scenarios and designing initiatives toward just transitions: coproducing knowledge with(in) the dried fish sector in the Indian Sundarbans - Ghosh, Raktima; Mukherjee, Jenia; Bandyopadhyay, Aishik; Chatterjee, Subhradeep; Choudry, Anuradha; Ghosh, Poulami; Pathak, Souradip; Sen, Amrita; Sinha, Priyadarsini (Frontiers in Water, 2023)
The south-western fringe of the Indian Sundarbans hosts a number of fish drying collectives that are exposed to a bundle of mutually reinforcing social-ecological-institutional risks. Despite its wide contribution to local-regional food security and livelihoods, dried fish production has received little attention in research and policy circles so far. As part of the Social Sciences and Humanities Research Council (SSHRC) sponsored Dried Fish Matters global partnership project, our research team seeks to address this lack in two ways: (i) delineating knowledge base through a systematic literature review on intersecting social-ecological and sociohydrological dimensions of integrated fisheries and fish drying practices, and (ii) employing a knowledge co-production approach that involves participation of dry-fishers, researchers, fishworkers' forum (partner organization), and scientists for meaningful understandings about the constraints and potentials in the sector. In this essay, we applied a three-step methodology to arrive at a crisscrossing conceptual, empirical, and collective understandings on the 'invisible' dried fish value chain in the Indian Sundarbans. With detailed lessons from the field, our interdisciplinary research team acts as a liaison among the groups to build a collaborative space for interactions, recognize prevalent adaptive practices and identify pathways toward short-, intermediate-, and long-term co-interventions through which fish drying practices can be more effectively improvised upon and up scaled. The essay lays out detailed insights and sensible recommendations from the knowledge co-production workshop, organized as a part of solution-focused participatory research on climate-resilient and gender-aware dried fish practices in the Indian Sundarbans. In light of the collective observations on the complex problems and reflections on needs-driven initiatives, the authors advocate for collaborative research praxes in forging just transitions for the less explored dried fish sector.